Juridical Analysis of Blasphemists of Religion Based on Criminal Perspective - Irawanto, Irawanto; Santiago, Faisal (Journal of World Science, 2023)
Indonesia is a heterogeneous and pluralist country, especially regarding religious diversity. Although different, all religions in Indonesia become one in the spirit of Bhinneka Tunggal Ika. However, the issue of blasphemy is considered taboo and very sensitive because it concerns interfaith and intertribal or ethnic interests. Therefore, the state is present to anticipate this problem with pre-prepared laws and regulations. So the purpose of this study is to find out and analyze related punishments and criminal violations related to blasphemy based on applicable legal regulations and theories in Indonesia. The method used is to study laws and regulations that are the primary references, books and legal journals as secondary material, and websites and social media as tertiary material. Indonesia's diverse society and democratic values demand that the country maintain harmony among different cultures. The state has prepared Article 156a to protect religion and its adherents, like other articles in the law. In blasphemy cases, the state should mediate and resolve disputes, punish violators, and support victims. Extensive discussions and analyses using various sources have been conducted about blasphemy cases.